Anaerobic Degradation of Phthalate Isomers by Methanogenic Consortia - Kleerebezem, Robbert (American Society for Microbiology, 1999)
Three methanogenic enrichment cultures, grown on ortho-phthalate, iso-phthalate, or terephthalate were obtained from digested sewage sludge or methanogenic granular sludge. Cultures grown on one of the phthalate isomers were not capable of degrading the other phthalate isomers. All three cultures had the ability to degrade benzoate. Maximum specific growth rates (μ(S)(max)) and biomass yields (Y(X(tot))(S)) of the mixed cultures were determined by using both the phthalate isomers and benzoate as substrates. Comparable values for these parameters were found for all three cultures. Values for μ(S)(max) and Y(X(tot))(S) were higher for growth on benzoate compared to the phthalate isomers. Based on measured and estimated values for the microbial yield of the methanogens in the mixed culture, specific yields for the phthalate and benzoate fermenting organisms were calculated. A kinetic model, involving three microbial species, was developed to predict intermediate acetate and hydrogen accumulation and the final production of methane. Values for the ratio of the concentrations of methanogenic organisms, versus the phthalate isomer and benzoate fermenting organisms, and apparent half-saturation constants (K(S)) for the methanogens were calculated. By using this combination of measured and estimated parameter values, a reasonable description of intermediate accumulation and methane formation was obtained, with the initial concentration of phthalate fermenting organisms being the only variable. The energetic efficiency for growth of the fermenting organisms on the phthalate isomers was calculated to be significantly smaller than for growth on benzoate.